EFEKTIVITAS ANTIBAKTERI EKSTRAK DAUN TEH HIJAU TERHADAP BAKTERI MYCOBACTERIUM TUBERCULOSIS - Misnarliah; Ernawati, Andi (Jurnal Biogenerasi, 2024)
Tuberculosis is still a global health problem. Prolonged treatment of tuberculosis and using several anti-tuberculosis drugs (OAT) can cause side effects, one of which is multidrug resistance. Cases of multidrug-resistant (MDR) and extensively drug-resistant (XDR) Mycobacterium strains continue to increase. . Research and development of active compounds from medicinal plants to achieve more effective tuberculosis treatment is still being promoted. This research aims to determine the potential and effectiveness of green tea plant (Camellia sinensis) leaf extract in inhibiting the growth of Mycobacterium tuberculosis strain H37Rv bacteria using the LJ (Lowenstein-Jensen) method in vitro. The research samples used were green tea plant leaves (Camellia sinensis) obtained from the Malino Village Tea Plantation, Tinggi Moncong Regency, Gowa District, South Sulawesi. The leaf extract was made in 4 types of concentrations, namely 10, 20, 50 and 100 µg/ml, each of which was tested against the clinical isolate of Mycobacterium tuberculosis strain H37Rv using the LJ (Lowenstein-Jensen) method as the standard for tuberculosis examination. Of the four extracts tested in vitro, only extract concentrations of 50 and 100 µg/ml were able to very strongly inhibit and kill the growth of Mycobacterium tuberculosis strain H37Rv (inhibition percentage of 100%), not a single bacterial colony growth was found during the observation period. The percentage of inhibition of green tea plant leaves (Camellia sinensis) is the same as the percentage of inhibition of the drug rifampicin. Thus, the leaves of the green tea plant (Camellia sinensis) with concentrations of 50 and 100 µg/ml have potential antituberculosis activity and are prospective to be developed as antituberculosis from natural ingredients, and also as an additional therapeutic complement for TB.